Early vs late intervention in twin reversed arterial perfusion sequence. (January 2014) - Berg, C.; Holst, D.; Mallmann, M. R.; Gottschalk, I.; Gembruch, U.; Geipel, A.
ABSTRACT Objective To compare two different management approaches in prenatally diagnosed twin reversed arterial perfusion (TRAP) sequence. Methods Retrospective analysis of all cases with TRAP sequence diagnosed in one center over a period of 10 years. Prior to 2010, all cases were managed expectantly until 19 weeks' gestation; thereafter, patients could choose either radiofrequency ablation (RFA) or expectant management (Group A). From 2010 onward all patients were offered interstitial laser at the time of diagnosis (12 weeks at the earliest) or expectant management (Group B). Results Forty cases were included in the study. In Group A, 23 cases were diagnosed at a mean gestational age of 19.9 ± 6.3 weeks. Sixteen patients were managed expectantly (13 survivors, 81%), while six underwent RFA at the time of diagnosis and one later in pregnancy (six survivors, 86%). In Group B, 17 cases were diagnosed at a mean gestational age of 16.4 ± 4.7 weeks. Six patients chose expectant management (five survivors, 83%) and 11 had interstitial laser therapy at the time of diagnosis (eight survivors, 73%). The loss rate of the pump twin was not significantly different between Group A and Group B (three of 23 vs four of 17; P = 0.3). In Group B the rates of preterm premature rupture of membranes (PPROM) and delivery < 34 weeks were significantly lower, and gestational age at birth as well as birth weight were significantly higher than in Group A. Conclusion Despite the limitations resulting from its retrospective design, our study on management of TRAP sequence adds some evidence in favor of prophylactic intervention by intrafetal laser from 12 weeks onward. Copyright © 2013 ISUOG. Published by John Wiley & Sons Ltd.